Smartphone Use, Experience of Learning Environment, and Academic Performance among University Students: A Descriptive Appraisal. (10th February 2022) - Faimau, Gabriel; Tlhowe, Kelebogile; Tlhaolang, Omphile
Abstract : In our contemporary digital society, the smartphone is at the center of a powerful technological revolution affecting multiple domains. In the context of higher learning, the use of smartphones among students has been an area of interest. Previous studies on smartphone use and academic performance have generally focused on measuring the impact that smartphone use has on the academic performance of students. The purpose of this study is to examine the extent to which gender differences and the experience of a particular learning environment contributes to the use of smartphones for academic purposes. Data were collected through the use of a standardized self-report questionnaire completed by 300 first-year and 203 fourth-year undergraduate students from the University of Botswana. Our analysis is guided by the following specific objectives: first, to explore gender and the patterns of smartphone use for academic purposes; second, to appraise the contributing value of the experience of a learning environment on the use of smartphones to enhance academic achievement; and third, to examine smartphone use and its possible contribution to the performance outcome of students. Overall, we argue that the use of a smartphone for academic purposes is partly influenced by the extent to which a student is familiar with or understands the multiple contexts that shape his/her learning environment. For further studies in the field of smartphone use and academic performance, we suggest using multiple methods of data collection to uncover how students attach meanings to the use of smartphones and the role of smartphone use in improving their academic performance outcomes.